Do inflammatory markers play a role in the detection of periprosthetic infections? - Topak, Duran; Salan, Ahmet; Doğar, Fatih; Nazik, Selçuk (Journal of Surgery and Medicine, 2020)
Aim: Periprosthetic joint infection after total hip or knee arthroplasty is one of the most feared complications. The aim of this study was to evaluate the efficacy of inflammatory biomarkers in identifying periprosthetic joint infection. Methods: This cross-sectional and bi-centered study included 131 patients, who had suspected prosthesis infection and underwent three-phase bone scintigraphy. Patients were divided into three groups according to the Musculoskeletal Infection Society criteria and scintigraphic study results: Group 1 comprised cases with prosthetic infection, Group 2 included aseptic loosening cases and Group 3 included cases with healthy prostheses. Results: White blood cell average was 11.5 (3.2) 109/L in group 1, 8. (2.1) 109/L in group 2 and 7.9 (2.1) 109/L in group 3, among which it was significantly higher in Group 1 compared to Groups 2 and 3, (P<0.001, P<0.001), while there was no significant difference between groups 2 and 3 (P=0.753). C reactive protein values (CRP) were 46.6 (50.0) mg/L in group 1, 18.8 (17.5) mg/L in group 2 and 15.3 (17.1) mg/L in group 3, significantly higher in group 1 than the other groups (P<0.001, P<0.001), and similar in Groups 2 and 3 (P=0.876). The mean erythrocyte sedimentation rate values did not differ significantly between the groups. Conclusion: The use of three-phase bone scintigraphy and inflammatory biomarkers such as C reactive protein and white blood cell have been shown to be effective in predicting prosthetic infection.